Nuclear Threats and Security Challenges - Apikyan, Samuel; Diamond, David (NATO Science for Peace and Security Series B: Physics and Biophysics, 2015)
With the dissolution of the Soviet Union the nuclear threats facing the world are constantly evolving and have grown more complex since the end of the Cold War. The diversion of complete weapon systems or nuclear material to rogue nations and terrorist organizations has increased. The events of the past years have proved the necessity to reevaluate these threats on a level never before considered.  In recognition that no single country possesses all of the answers to the critical scientific, institutional and legal questions associated with combating nuclear and radiological terrorism, the NATO Advanced Research Workshop on "Preparedness for Nuclear and Radiological Threats" and this proceeding was structured to promote wide-ranging, multi-national exploration of critical technology needs and underlying scientific challenges to reducing the threat of nuclear/radiological terrorism; to illustrate through country-specific presentations how resulting technologies were used in national programs; and to outline the role of legal, policy and institutional frameworks in countering nuclear/radiological terrorism. One key outcome of this book is better understanding of the interdependent contributions from across the international community of the scientific and technological components and the legal, policy and institutional components to combating nuclear and radiological threats.